Sex Disparities in Pediatric Acute Rhinosinusitis: A National Perspective. (8th February 2022) - Shah, Vraj P.; Haimowitz, Sean Z.; Desai, Amar D.; Barron, Kendyl; Patel, Prayag; Fang, Christina H.; Grube, Jordon G.; Baredes, Soly; Eloy, Jean Anderson
Abstract : Objective: This study aims to provide an age‐stratified analysis of associations with patient sex in pediatric inpatients with acute rhinosinusitis (ARS). Study Design: Retrospective cohort study. Setting: National administrative database. Methods: The 2016 Kids' Inpatient Database was queried for pediatric inpatients (<21 years old) with ARS ( ICD‐10 J01). Orbital and intracranial sequelae were selected via ICD‐10 codes. Statistical associations by sex were determined via univariate and multivariable analyses. Weighted measures are reported to provide national estimates. Results: Of the 5882 patients identified with ARS, 2404 (40.9%) were female and 3478 (59.1%) were male. Male patients were younger than female patients (mean, 9.3 vs 9.9 years; P <. 001). Multivariable analysis indicated that males and females had similar total charges (71, 094 vs 66, 892, P =. 464) and length of stay (5.8 vs 6.1 days, P =. 263). However, male patients underwent more procedures (1.8 vs 1.5, P <. 001). Mortality was similar between male and female patients (odds ratio [OR], 0.91; P =. 664). Male patients also had increased odds for having orbital (OR, 1.58; P <. 001) and intracranial (OR, 1.99; P <. 001) complications. Differences in sex‐dependent sequela risk were starkest in patients aged 14 to 20 years, with male patients being more likely to have orbital (OR, 2.91; P <. 001) and intracranial (OR, 3.86; P <. 001) complications. Conclusion: In a cohort of pediatric inpatients with ARS, males have increased odds for orbital and intracranial sequelae and undergo more procedures than females. However, males and females have similar charges and length of stay. Our study highlights age‐stratified differences in ARS across patient sex.